Editorial do Volume 1 Número 1 - Vieira, Kelmara Mendes; Coronel, Daniel Arruda; Bender Filho, Reisoli (Práticas de Administração Pública, 2017)
Editorial do volume 1 , número 1, da PAP- Práticas de Administração Pública